Genetic Association of FERMT2, HLA-DRB1, CD2AP, and PTK2B Polymorphisms With Alzheimer’s Disease Risk in the Southern Chinese Population - Yan, Yi; Zhao, Aonan; Qui, Yinghui; Li, Yuanyuan; Yan, Ran; Wang, Ying; Xu, Wei; Deng, Yulei (Frontiers in Aging Neuroscience, 2020)
Objectives This study aimed to explore the relationship between 18 single nucleotide polymorphisms (SNPs) and Alzheimer’s disease (AD) within the southern Chinese population. Methods A total of 420 participants, consisting of 215 AD patients and 205 sex- and age-matched controls, were recruited. The SNaPshot technique and polymer chain reaction (PCR) were used to detect the 18 SNPs. Combined with the apolipoprotein E (APOE) ε4 allele and age at onset, we performed an association analysis between these SNPs and AD susceptibility. Furthermore, we analyzed SNP-associated gene expression using the expression quantitative trait loci analysis. Results Our study found that rs17125924 of FERMT2 was associated with the risk of developing AD in the dominant (P = 0.022, odds ratio [OR] = 1.57, 95% confidence interval [CI]: 1.07–2.32) and overdominant (P = 0.005, OR = 1.76, 95% CI: 1.18–2.61) models. Moreover, compared with APOE ε4 non-carriers, the frequency of the G-allele at rs17125924 was significantly higher among AD patients in APOE ε4 allele carriers (P = 0.029). The rs9271058 of HLA-DRB1 (dominant, overdominant, and additive models), rs9473117 of CD2AP (dominant and additive models), and rs73223431 of PTK2B (dominant, overdominant, and additive models) were associated with early onset AD (EOAD). Using the genotype-tissue expression (GTEx) and Braineac database, we found a significant association between rs9271058 genotypes and HLA-DRB1 expression levels, while the CC genotype at rs9473117 and the TT genotype of rs73223431 increased CD2AP and PTK2B gene expression, respectively. Conclusion Our study identifies the G-allele at rs17125924 as a risk factor for developing AD, especially in APOE ε4 carriers. In addition, we found that rs9271058 of HLA-DRB1, rs9473117 of CD2AP, and rs73223431 of PTK2B were associated with EOAD. Further studies with larger sample sizes are needed to confirm our results.